2005
DOI: 10.1097/01.jnen.0000173893.01929.fc
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes Produce Dendritic Cell-Attracting Chemokines In Vitro and in Multiple Sclerosis Lesions

Abstract: As a result of their close association with the blood-brain barrier, astrocytes play an important role in regulating the homing of different leukocyte subsets to the inflamed central nervous system (CNS). In this study, we investigated whether human astrocytes produce chemokines that promote the migration of myeloid dendritic cells (DCs). By reverse transcriptase-polymerase chain reaction and enzyme-linked immunosorbent assay, we show that cultured human astrocytes stimulated with interleukin-1beta and tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
117
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(124 citation statements)
references
References 66 publications
5
117
1
1
Order By: Relevance
“…Inhibition of the interactions of CXCL12 and its receptor CXCR4 by AMD3100 is associated with widespread parenchymal invasion of mononuclear cells in EAE (30). (iii) CXCL12 attracts immature dendritic cells with anti-inflammatory properties into the CNS (36). (iv) Finally, CXCL12 is able to redirect already differentiated Th1 cells into anti-regulatory T-cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the interactions of CXCL12 and its receptor CXCR4 by AMD3100 is associated with widespread parenchymal invasion of mononuclear cells in EAE (30). (iii) CXCL12 attracts immature dendritic cells with anti-inflammatory properties into the CNS (36). (iv) Finally, CXCL12 is able to redirect already differentiated Th1 cells into anti-regulatory T-cells (29).…”
Section: Discussionmentioning
confidence: 99%
“…(Christian et al, 1996), we have found no evidence for the presence of plasmacytoid dendritic cells during the first 14 days after VSV infection (Palian et al, unpublished). Indeed, pDCs are reportedly absent from the brain parenchyma, but have been found in brain during chronic inflammation (Ambrosini et al, 2005;Bailey et al, 2007;Matyszak and Perry, 1997;Newman et al, 2005;Rosicarelli et al, 2005;Serafini et al, 2006;Zozulya et al, 2007). IFN-producing cells do not enter the CNS at early times after infection by wt VSV, and peripheral IFN does not cross the blood-brain barrier efficiently (Dafny and Yang, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, CCL2, CCL3, CCL5, and CXCL10 seem to play an important role in the recruitment of T cells and macrophages, acting via CCR2, CCR1, CCR5, and CXCR3, respectively. [1][2][3][4][5][6][7][8][9] More recently, CXCL12 and CCL20 have been shown to attract immature dendritic cells to MS lesions, 12 whereas CXCL13 appeared to direct B-cell recruitment into the CNS, 10,11 and CXCL13-deficient mice have a mild, selflimiting form of EAE. 60 In addition to a pro-inflammatory role, chemokines might also have regulatory effects within the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…6 -9 Recently, CXCL13 has been linked to B-cell recruitment in MS 10 and EAE, 11 and immature dendritic cells might be attracted to MS lesions in response to CXCL12 and CCL20. 12 Chemokine receptors have also been localized on resident CNS cell types but the role of these receptors is yet to be fully elucidated. [13][14][15][16][17][18][19][20][21][22][23][24][25] In MS, oligodendrocytes are a primary target and are severely depleted in affected areas.…”
mentioning
confidence: 99%